Synthesis of new glyoxime derivatives, characterization and investigation of their complexes with Co(II), Ni(II), and Cu(II) metals and thermal studies - Özkan, EG; Canpolat, E; Kaya, M (Pleiades Publishing Ltd, 2005)
In this study, two new vic-dioxime ligands and their complexes with Co2+, Ni2+, and Cu2+ ions were synthesized. Secondary amines (morpholine and piperidine) reacted with anti-chloroglyoxime to give morpholineglyoxime (H2L1) and piperidineglyoxime (H2L2) ligands. All the complexes have a metal to ligand ratio of 1 : 2. The structure of the ligands and their complexes was proposed from elemental analyses, IR, UV-VIS, H-1 and C-13 NMR spectra, conductivity, magnetic susceptibility measurements, and thermogravimetric analyses.
Keywords: Vic-Dioxime; Mononuclear Complexes; Reactivity; Oxime; Zn(Ii); Nickel; Ligands; Cd(Ii); Stereoisomers; (E,E)-Dioxime